A mental health outreach program in child welfare centre with homoeopathy - Muraleedharan, K. C.; Moorthi, S. K.; Gilla, Deepthi (International Journal Of Community Medicine And Public Health, 2023)
Mental health problems during childhood and adolescence are a major health concern globally. Children in welfare centres pose varied emotional and behavioural problems (EBP) and need special treatment with a multidisciplinary approach. Homoeopathy has an evidence base for effectiveness in the management of some behavioural problems in children. Objective was to evolve the approach to mental health intervention using homeopathic medicines in the management of behavioural issues in children at a child welfare centre (CWC) through an outreach initiative. A screening program was conducted on 46 children at a child welfare centre, out of which 20 children were diagnosed with mental health issues according to ICD-10 criteria. These children were treated with individualised homoeopathic medicines and are followed up in regular intervals to assess the changes in behaviour of children after homoeopathic intervention. 3 cases of conduct disorders are illustrated to show the constitutional approach in children with behavioural problems. Causal attribution to the outcome after intervention are described as per Monarch criteria. 85% of cases were found to have moderate to marked improvement after 1 year of treatment. The remedies indicated are Sulphur (6), Carcinosinum (3), Natrum Mur (3), Silicea (2), Lachesis, Lycopodium, Merc Sol, Phosphorus, Staphysagria and Tarantula hispanica. Individualized homoeopathic medicines are found to be useful in the management of EBP of children in CWC. This preliminary mental health outreach serves as a model for future pragmatic research. Studies with appropriate study designs focussing on specific behavioural problems in juvenile delinquents are suggested.